Capacitance Analysis of Transient Behavior Improved Metal-Insulator-Semiconductor Tunnel Diodes With Ultra Thin Metal Surrounded Gate - Sung-Wei Huang (IEEE, 2021)
The metal-insulator-semiconductor tunnel diodes with ultra thin metal surrounded gate (UTMSG) have been found to have improved transient current behavior, and the improvement is proportional to the area of the surrounding gate. The resistance induced by the thin metal gate leads to delay of inversion carriers under the surrounding gate. At the same time, the UTMSG devices could read the capacitance under the surrounding gate only in inversion regime, but not in accumulation and depletion regime. This could be explained by a proposed small signal circuit model. The large resistance within the metal gate blocks the AC signal coming from the surrounding gate. On the other hand, the increased inversion carrier density introduces an inversion channel, which will let the AC signal pass through. The successful reproduction of the experimental observed unusual capacitance-voltage characteristics by TCAD simulation proves the proposed model as well. Detailed simulations are implemented by varying different parameters to give a further understanding of the UTMSG device. A rough estimation of the resistance of the inversion channel is also given. The calculation shows the consistency with the proposed small signal circuit model. The UTMSG device could experience a larger change of magnitude of capacitance and hence a larger capacitance window when switching from 1 V to −0.3 V, verified by simulation. The simulation has also shown that the edge thickened oxide will only slightly modulate the capacitance of the UTMSG devices.